Mitochondrial portraits of the Madeira and Açores archipelagos witness different genetic pools of its settlers - Brehm, A (2003)
We have studied the matrilineal genetic composition of the Madeira and Açores north Atlantic archipelagos, which were settled by the Portuguese in the 15th century. Both archipelagos, and particularly Madeira, were involved in a complex commercial network established by the Portuguese, which included the trading of slaves across the Atlantic. One hundred and fifty-five mtDNAs sampled from the Madeira and 179 from the Açores archipelagos were analysed for the hypervariable segment I (HVS-I), and for haplogroup-diagnostic coding-region RFLPs. The different settlement histories of both groups of islands are well reflected in their present day mtDNA pool. Although both archipelagos show identical diversity values, they are clearly different in their haplogroup content. Madeira displays a stronger sub-Saharan imprint, with haplogroups L1-L3 constituting about 13% of the lineages. Also, the relative frequencies of L sub-clusters in Madeira and mainland Portugal suggests that, at least in part, African presence in Madeira can be attributed to a direct gene flow from West Africa and not via Portugal. A comparison of the genetic composition of these two archipelagos with the Canary Islands, specially taking into account that their European source population was essentially from the Iberian Peninsula, testifies the stronger impact of the North African U6 cluster in the Canaries. This group is present in Madeira at a moderate frequency, but very reduced in the Açores. Nevertheless the recorded introduction of Canary native Guanches, who are characterized by the presence of particular sub-clade U6b1, has left no detectable imprints in the present day population of Madeira.